2017
DOI: 10.1007/s00262-017-2016-9
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine release of IL-2 and anti-CTLA-4 enhances the ability of artificial polymer antigen-presenting cells to expand antigen-specific T cells and inhibit tumor growth in a mouse model

Abstract: Accumulating evidence indicates that bead-based artificial antigen-presenting cells (aAPCs) are a powerful tool to induce antigen-specific T cell responses in vitro and in vivo. To date, most conventional aAPCs have been generated by coupling an antigen signal (signal 1) and one or two costimulatory signals, such as anti-CD28 with anti-LFA1 or anti-4-1BB (signal 2), onto the surfaces of cell-sized or nanoscale magnetic beads or polyester latex beads. The development of a biodegradable scaffold and the combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In addition, the heterogeneity of HHLA2 function was also observed in the co-culture experiment, the T lymphocytes from different donors showed a different response to the HHLA2 protein in cytokine production (17). This contradictory phenomenon is interesting, but also confusing for the further researches on HHLA2 (1821).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the heterogeneity of HHLA2 function was also observed in the co-culture experiment, the T lymphocytes from different donors showed a different response to the HHLA2 protein in cytokine production (17). This contradictory phenomenon is interesting, but also confusing for the further researches on HHLA2 (1821).…”
Section: Introductionmentioning
confidence: 96%
“…First promising in vivo experiments in mice demonstrated that combining aAPC technology with anti-PD-1 ICI immunotherapy synergistically stimulated antigen-specific proliferation of cytotoxic T cells, delayed murine melanoma growth, and extended survival, while either treatment alone had no effect [ 83 ]. Equally, injection of aAPC particles loaded with both IL-2 and anti-CTLA-4 outperformed conventional single-release aAPCs, efficiently promoted sustained ICI and IL-2 release as well as antigen-specific T cell activation and expansion, and inhibited tumor growth in a murine melanoma model [ 110 ]. To make aAPCs even more versatile, Zhang and colleagues developed a multipotent artificial antigen-presenting cell (MaAPC) [ 111 ].…”
Section: Nano-sensitizing the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…In this context, it has been additionally shown that more sustained release of cytokines elicits a stronger immune response. Lastly, these aAPC platforms have also been used to deliver immunosuppressive blocking antibodies and showed promising results in delayed tumor growth (Eggermont et al, 2014;Zhang et al, 2017a).…”
Section: Artificial Apcs (Aapcs)mentioning
confidence: 99%